A Simulative Comparison of AODV and DSR On-Demand Routing Protocols for Mobile Ad-Hoc Networks - Nordin, Simbak; Ragb, O. M. Saleh; Md Yazid, Mohamad Saman (2014)
Mobile Ad-hoc NETwork is a collection of two or more mobile nodes that has no infrastructure support, and every mobile node can work as a router. In MANET mobile nodes can move arbitrarily, consequently the system topology changes in random manner. Practically, in order to allow mobile nodes to communicate with each other, a routing protocol is desired to discover routes between nodes, and determines how information is transmitted from a source node to a destination node. Basically, MANET routing protocols are classified into two categories: On-demand and Table-driven. On-demand protocols are utilized whenever a communication is needed. The most widely researched on-demand MANET protocols: DSR (Dynamic Source Routing protocol) and AODV (Ad hoc On-demand Distance Vector protocol). Objective: The main aim of this paper is to simulation based analysis of DSR and AODV protocols on the basis of different performance metrics which are packet delivery fraction (PDF), routing overheads (RO), and end-to-end delay. The simulation is performed through the simulation tool Global Mobile Simulator due to its open source simplicity and free availability. Results: in considered mobility scenarios, AODV gives better PDF than DSR, while DSR gives better RO and End-to-End delay in most mobility scenarios. Conclusion: In this article, an effort has been made to concentrate on the comparative study of well known on-demand protocols (AODV and DSR). Consequently, a single MANET routing protocol cannot accomplish best in all circumstances. Therefore, the preference of MANET routing protocol should be done carefully according to the conditions of the definite application.